Why do South Africans use stokvels and what are the barriers that prevent participation in the formal financial sector? - Gwamanda, Mbali (College of Accounting, 2020)
Two and a half billion of the world’s working adults are excluded from financial services. The exclusion of people from the formal financial sector has led to the growth of microfinance globally. The importance of financial inclusion is represented through the Sustainable Development Goals in which financial inclusion is an enabler in seven of the 17 goals. In South Africa, stokvels are one of the most important microfinance phenomena, as 11.5-million people are part of a stokvel. The formal financial sector in South Africa has started to target stokvel members through various stokvel accounts and products. Previous literature on stokvels focuses on the demography of stokvels; the features of stokvels; and the history of stokvels. Previous studies have found that the formal sector does not understand stokvel clientele. However, the review of the literature indicates that there is an insufficient analysis of the needs of stokvel members and the how the formal sector can better accommodate their needs. Therefore, this study will explore why South Africans continue to use stokvels and what barriers prevent stokvel members from participating in the formal financial sector. Recommendations will be made to various stakeholder based on the themes identified. This study found that the stokvel members perceived there to be information asymmetry, which they believe is then exploited by the banks. As a result, there is distrust in the formal financial system. Moreover, this study also found that the social interactions in stokvels are changing due to technology. The findings and recommendations in this study can be used by banks and other formal financial institutions to improve the suitability of their product and services. Consequently, financial inclusion will improve as the products and services provided by the formal sector will be better suited to the needs of stokvel members. This study will also provide insights for the South African government, community leaders and The National Stokvel Association of South Africa (NASASA).